Comprehensive performance analysis of a flat plate solar water heating system featuring a dual-inlet modified absorber - Elumalai Vengadesan; K. Gnanasekaran (Discover Sustainability)
Abstract Flat plate solar water heater (FPSWH) is the most commonly used solar water heating system in domestic and commercial sectors due to its simple operation and cost-effectiveness. However, the water temperature range is limited due to the poor heat absorption and higher heat loss, which is controlled by the absorber geometry and inlet water temperature. Hence, this study aims to improve the useful heat absorption and reduce heat loss in FPSWH by incorporating an additional inlet on the modified absorber. The inlet sections at the top and bottom of the absorber allow low-temperature water to enter, while the baffles guide the flow in a serpentine pattern. Finally, the heated water exits through a common outlet at the center of the absorber. The combination of low inlet water temperature and an enhanced fluid flow path improves heat absorption efficiency. A real-time experimental test result of this study shows that the absorber temperature is reduced through improved temperature distribution, lowering heat loss by 3.8–4.2% compared to a single inlet absorber. The average heat transfer coefficient and Nusselt number are 451 W/m2K and 17, respectively, representing increases of 15.3% and 15.4% over the single inlet absorber. Furthermore, energy and exergy efficiencies of 87% and 7.3% are achieved, which are 18.2% and 23.7% higher than those of the single inlet absorber, respectively. The economic and environmental analysis indicates that the higher annual useful energy (13.2–25%) of the dual inlet absorber leads to a shorter payback time and greater CO2 emission mitigation compared to the single inlet absorber.